1972
DOI: 10.1002/bit.260140502
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic components of alkaline proteases of Bacillus strains. Zymograms and electrophoretic isolation

Abstract: SummaryCharacterization of proteolytic activity in preparations or fermentation broth is accomplished by methods based on a combination of disc electrophoresis and visualization of the activity. The methods permit a direct comparison with reference preparations. All alkaline proteases studied, including the three subtilisins, were found to consist of several proteolytic components. The zymograms of the subtilisin type preparations show an irregular pattern. At least 14 different components may be observed, bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The molecular mass of the protease determined by SDS-PAGE was 29.4 kDa, while an IEFzymogram performed with high pH range carrier ampholytes (Pharmalyte 8-10.5, Pharmacia) showed that its pI was >10.3 (data not shown). These properties resembled those of the highly alkaline protease group produced by alkaliphilic bacilli, which includes enzymes with a low molecular mass of 26-28 kDa and high optimum pH for activity and pI values (Zuidweg et al 1972;Betzel et al 1992;Kobayashi et al 1995). When the protease solution was analysed under non-reducing conditions, the active band showed a slightly higher apparent molecular mass.…”
Section: Resultsmentioning
confidence: 91%
“…The molecular mass of the protease determined by SDS-PAGE was 29.4 kDa, while an IEFzymogram performed with high pH range carrier ampholytes (Pharmalyte 8-10.5, Pharmacia) showed that its pI was >10.3 (data not shown). These properties resembled those of the highly alkaline protease group produced by alkaliphilic bacilli, which includes enzymes with a low molecular mass of 26-28 kDa and high optimum pH for activity and pI values (Zuidweg et al 1972;Betzel et al 1992;Kobayashi et al 1995). When the protease solution was analysed under non-reducing conditions, the active band showed a slightly higher apparent molecular mass.…”
Section: Resultsmentioning
confidence: 91%
“…Earlier work (Zuidweg et al, 1972;Verbruggen etal., 1974;Verbruggen &Baeck, 1975) demonstrated considerable electrophoretic heterogeneity in commercial crystalline subtilopeptidase A. Autodigestion and Ca2+-binding effects could be excluded as the cause of this heterogeneity. Commercial enzyme preparations were also shown to be immunochemically heterogeneous (Verbruggen et al, 1974;Belin et al, 1970).…”
mentioning
confidence: 94%
“…221 (3). The high-alkaline protease group, including Savinase (4), PB92 (5), and M-protease (6) that are all produced by alkaliphilic bacilli, has a low-molecular-mass of 26 -28 kDa. They are used mainly in the detergent industry.…”
mentioning
confidence: 99%